Optimisation of cryovials and milt dilution ratios to upscale carp sperm cryopreservation for use in hatchery seed production: Upscaling of Carp Sperm Cryopreservation - Kumar, Santosh; Kumar, Aditya; Rama Shankar Sah; Ajay Kumar Singh; Ajay Yadav; Arvind Verma; Deepti Negi; Hayin Tamut; Kuldeep Kumar Lal (Indian Journal of Fisheries, 2023)
This study reports the experimental results carried out to optimise containers and miltdilution ratios for carp sperm cryopreservation, in order to make the process simple andcompatible with the needs of commercial carp seed production, which is a small-scale andlow technology sector in Asia. The procedure optimisation for up-scaling was assessedby the ability of cryopreserved sperms to fertilise Cyprinsu carpio eggs and hatchingpercentage, in three different experiments. In the first experiment, we tested the effect ofmilt to different extender dilutions (1:4, 1:6 and 1:8); the second experiment tested theeffect of container capacities (0.5 ml French straw; 2 ml and 5 ml cryovials) with two dilutionratios (1:3 and 1:6) and in the third experiment, the efficacy of pre-mix of extender salts andindividually pre-weighed salts stored over 5 months was compared with fresh preparationof extender. Out of the three dilutions tested, two dilutions viz., 1:4 and 1:6, yielded hatchingabove 50%. We also used the milt cryopreserved at dilution of 1:3 which was post-thawdiluted with extender, to make final dilution of 1:6, to fertilise the eggs. This post-thawdilution in the ratio 1:6, yielded the results comparable to the milt cryopreserved in 1:6dilution. This approach can help small-scale seed producers to store more sperm withinthe limits of the cost of liquid nitrogen. The extender salt composition, pre-weighed andpre-mixed, was also found to give comparable results to the fresh composition after storageover 5 months. This can assist in developing ready to use, cost-effective, working kitsavailable to semi-technical hatchery seed producers. The parameters optimised in the studyhas potential to be transformed as an easy strategy with the use of 5 ml vial, cryopreservedat 1:3 dilution, with further post-thaw dilution at site, thus aiding in fertilisation of largevolume of eggs produced by high fecund carp species within the limited time available formaintaining good gamete quality.Keywords:Cryobanking, Cryovials, Dilution, Salt premix